Self-reports and peer-assessments of shyness and assertivenes - Bratko, Denis (Array, 2002)
High school students (N=336 ; 67% females) were asked to assess themselves and their peers on questionnaire measuring shyness and assertiveness (Zarevski & Vukosav, 1997). Factor analysis clearly differentiates self-resports on these constructs. Peer-assessments show less clear differentiationbetween shyness and assertiveness and presence of a strong halo-effect. Namely, the ratio between 1st and 2nd Eigen value extracted from correlation matrix with items measuring shyness and assertiveness is much greater for peer-assessments than for self-reports (in female sample variances explained with first two Eigen values for peer reports were 23%:6% and for self-reports 14%:10% for males respective values were 27%:7% and 14%:7%). The strong halo-effect in peer-assessments is also reflected in high internal homogeneity. Correlations between self-ratings and peer-assessments are higher for shyness (rfemale =.37, rmale=.35) than assertiveness (rfemale=.31, rmale=.20).